Normas jurídicas, expectativas normativas e seus respectivos conceitos do direito: uma análise comparativa entre conceitos das teorias do Direito de Hans Kelsen e Niklas Luhmann - Back, Mateus Di Palma (Universidade do Vale do Rio dos Sinos, 2016)
This is a dissertation which compares the concepts of law as presented by categories of diferent theories of Law. The concept of legal norm described by Hans Kelsen and the concept of normative expectations described by Niklas Luhmann have in common only the fact that they are the product of observations aimed at a normative reality. Their similarities end there. In this sense, Kelsen’s legal norm is marked by the difference between factual and normative, while Luhmann’s normative expectation is marked by the difference between cognitive and normative. These categorizations are not directly comparable, however, to the extent that both of these concepts are used by the authors for their descriptions of the law, these concepts become, in their difference, representative of the difference between the concepts of Law underlying them. This work intends to make use of them to carry out a comparative analysis of both descriptions: between Kelsen’s normative concept of law and Luhmann’s sociological one. It will be a bibliographical and comparative work. The way to do this is as follows: at first it will be presented the fundamentals of the descriptive mode of Kelsen’s theory of law; a second phase will present the fundamentals of the descriptive way of Luhmann’s sociology of law; in the end, it will be sought to derive, from the key concepts mentioned, those concepts of law underlying them for the purpose of oposing the different ways of observing the law. As a result of the research, it was concluded that, although it is really a comparison between an analytical concept with a functional one, differences related to the concepts could not be summarized to the transdisciplinary potential of theories, but to a choice of how to approach the object of research.
Keywords: Norma jurídica; Expectativa normativa; Teoria do direito; Sociologia do direito; Transdisciplinariedade; Hans Kelsen; Niklas Luhmann; Legal norm; Normative expectation; Theory of law; Sociology of law; Transdisciplinarity; ACCNPQ::Ciências Sociais Aplicadas::Direito